Coopetition under alliance? Applying awareness-motivation-capability competitive dynamics perspective - Chang, Wei-Lun; Chiu, Chia-Ling (Journal of Business Economics and Management, 2016)
Airline companies join airline alliances to cope with the high level of competition in the airline industry. However, pressure within an alliance is substantial. This study used competitor mapping and awareness-motivation-capability competitive dynamics to analyze airline alliances. The results revealed that alliances compete to recruit airline companies, and the power differences in the alliances are considerable; only a few of the airline companies within the alliance possess power. In addition, we interviewed 2 senior managers to confirm the results of the analysis. A detailed content analysis was performed to test each hypothesis. The findings revealed that companies with low market commonality and high resource similarity can cooperate through resource allocation. We also discovered that the main competitive action was derived from disallowing local airline companies to join an alliance. Leading companies in the alliance generally negotiated for the entire alliance indirectly. This research suggests that companies cooperate not only to control cost but also to increase service quality.